Like Mother, Like Daughter. Intergenerational Transmission of Infant Mortality Clustering in Zeeland, the Netherlands, 1833-1912 - Ingrid K. van Dijk; Kees Mandemakers (Historical Life Course Studies)
The burden of infant mortality is not shared equally by all families, but clusters in high risk families. As yet, it remains unclear why some families experience more infant deaths than other families. Earlier research has shown that the risk of early death among infants may at least partially be transmitted from grandmothers to mothers. In this paper, we focus on the intergenerational transmission of mortality clustering in the Netherlands in the province of Zeeland between 1833 and 1912, using LINKS Zeeland, a dataset containing family reconstitutions based on civil certificates of birth, marriage and death. We assess whether intergenerational transmission of mortality clustering occurred in Zeeland, and if so, whether it can be explained on the basis of the demographic characteristics of the families in which the infants were born. In addition, we explore the opportunities for comparative research using the Intermediate Data Structure (IDS). We find that mortality clustering is indeed transmitted from grandmothers to mothers, and that the socioeconomic status of the family, the survival of mothers and fathers, and the demographic characteristics of the family affected infant survival. However, they explain the heterogeneity in infant mortality at the level of the mother only partially.